The interception of organic chemistry and agriculture: a review of new method sustainable crop production - Ansar Bilyaminu Adam; Danladi Mudwa Dwanga; Emmanuel Kingsley Chinedu; Musa Yahaya Abubakar; Abubakar Aminu; Aboh Mbo Joseph (Romanian Journal of Ecology & Environmental Chemistry)
The interception between organic chemistry and agriculture has transformed agricultural practices by producing creative answers for sustainable crop production. This thorough analysis explores the most recent developments in organic chemistry and their applications to agriculture, emphasizing cutting-edge techniques for increasing crop yields, strengthening plant disease resistance, and reducing environmental impact. We investigate the synthesis of organic chemicals to produce bioactive substances, such as biopesticides, bio-stimulants, and plant growth regulators. These substances have demonstrated significant potential in enhancing plant development, elevating stress resilience, and diminishing dependence on artificial fertilizers and insecticides. In addition, we look at how organic chemistry is used to create sustainable agricultural systems that make use of renewable resources, eco-friendly production techniques, and green chemistry concepts.